Compact UWB antenna design for MIMO applications - Kasi B.; Manickam G.V.; Chakrabarty C.K. (Maxwell Science Publications, 2023)
In this study, a compact printed Multiple-Input-Multiple-Output (MIMO) antenna with a dimension of 3270 mm2 has been proposed for Ultra-Wideband (UWB) systems applications. The design constitutes of two identical UWB antenna elements, which is etched onto a Taconic TLC-30 printed circuit board. The proposed antenna has been designed and simulated using computer simulation software. For validation purposes, antenna prototype is fabricated and tested. The UWB-MIMO antenna yields an impedance bandwidth of 2.9 to 12 GHz with a return loss of less than-10 dB. Furthermore, the isolation characteristic between the two antenna elements is more than 15 dB within the operating frequency range. The designed structure is found to provide good MIMO/diversity characteristic across the UWB band. Maxwell Scientific Organization, 2013.